Ultra-high performance concrete and its preparation method and application
By using modified montmorillonite nanosheets to form strong supramolecular compounds in ultra-high performance concrete, the problem of bottlenecks in improving the anti-invasion performance of ultra-high performance concrete is solved, and the effect of significantly improving the anti-invasion and mechanical properties is achieved.
Patent Information
- Application Number
- CN202510080569.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-20
AI Technical Summary
After the compressive strength of ultra-high performance concrete has been increased to a certain threshold, its anti-invasion performance has not been effectively improved, there is a platform effect, and there is a lack of effective means to improve the van der Waals force and the microcracks of the pores inside the material.
By adding montmorillonite nanosheets modified with phytic acid and urea to ultra-high performance concrete, a strong supramolecular compound (CPN) is formed, which improves the microstructure and hydration product network, improves early strength and hydration rate, and thus improves the anti-invasion performance.
The anti-invasion and mechanical properties of ultra-high performance concrete are significantly improved. By improving the microstructure and hydration product network, the combination of interface transition zones is enhanced, pores and gaps are filled, and the production of corrosive compounds is inhibited.
Smart Images

Figure CN119528522B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of building materials, and in particular relates to an ultra-high performance concrete and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Ultra-High Performance Concrete (UHPC) is a new type of cement-based composite material with ultra-high strength, high toughness and high durability. Compared with ordinary concrete, ultra-high performance concrete has significant advantages in terms of penetration and explosion resistance: under the same penetration conditions, its penetration depth and degree of pit damage are much smaller than ordinary concrete. However, with the continuous improvement of the strength of ultra-high performance concrete, when its compressive strength is increased to a certain threshold, the continued increase in compressive strength above the threshold cannot be effectively converted into anti-penetration performance, that is, there is a platform effect.
[0004] Existing research believes that the bottleneck in improving the penetration resistance of ultra-high performance concrete can be attributed to the following reasons: on the one hand, in order to improve the homogeneity of the material, the coarse aggregate that is beneficial to the penetration resistance was eliminated during the preparation process of the initial UHPC; although the UHPC containing coarse aggregate developed later improved the penetration resistance to a certain extent, the addition of coarse aggregate also introduced a relatively weak aggregate-matrix interface transition zone, which limited the further improvement of the penetration resistance; on the other hand, the main hydration product of the ultra-high performance concrete matrix is calcium silicate hydrate gel (CSH), and about 1 / 3 of the calcium silicate hydrate gel is connected by weak van der Waals forces, and only very low energy is required to make this connection mechanism invalid; and during the formation of CSH gel, the material will expand or contract. This volume change will produce stress concentration when constrained, leading to the formation of microcracks, thereby limiting the penetration resistance of the ultra-high performance concrete matrix.
[0005] In recent years, high-strength and high-hardness coarse aggregates (such as sintered bauxite coarse aggregates) have been successfully introduced into ultra-high performance concrete to improve its anti-penetration performance, especially to reduce the penetration depth. However, there is still a lack of effective means to limit the van der Waals force and the micro-cracks in the pores of the material, which limits the promotion and application of ultra-high performance concrete in protective engineering. Summary of the invention
[0006] In order to address the deficiencies of the prior art, the purpose of the present invention is to provide an ultra-high performance concrete and a preparation method and application thereof, wherein the ultra-high performance concrete matrix is modified by using montmorillonite nanosheets to form a denser microstructure and a hydration product network, thereby improving the early strength and hydration rate of the cement-based matrix, thereby improving its anti-penetration performance under the action of high-speed projectiles.
[0007] In order to achieve the above object, the technical solution of the present invention is:
[0008] In a first aspect, the present invention provides an ultra-high performance concrete, which is prepared from the following raw materials in parts by weight:
[0009] 1417-1517 parts of cement, 135-165 parts of silica fume, 35-43 parts of steel fiber, 21.16-63.48 parts of montmorillonite nanosheets, 410-510 parts of water and 8-14 parts of water reducing agent;
[0010] The montmorillonite nanosheets are modified by phytic acid and urea.
[0011] Optionally, the ratio of the montmorillonite nanosheets, phytic acid and urea is (1-2) g: (2-5) mL: (2-5) g.
[0012] Optionally, the cement is 52.5 grade or 52.5R grade Portland cement or ordinary Portland cement.
[0013] Optionally, the amorphous silicon dioxide content in the silica ash is greater than 95wt%, and the specific surface area of the silica ash is greater than 21.0m 2 / g, specific density is greater than 2.2.
[0014] Optionally, the steel fiber is a copper-plated straight steel fiber with an average length of 13 mm and an average diameter of 0.16 mm.
[0015] Optionally, the water reducer is a polycarboxylic acid-based high-efficiency water reducer.
[0016] In a second aspect, the method for preparing the ultra-high performance concrete comprises the following steps:
[0017] S1, mixing montmorillonite nanosheet raw material, phytic acid and urea in a set ratio, heating to 120-150° C. in an oxygen-free environment and stirring to obtain montmorillonite nanosheets;
[0018] S2, mixing cement and silica fume to obtain a first mixture;
[0019] S3, adding the aqueous dispersion of montmorillonite nanosheets and a water reducing agent to the first mixture, stirring to obtain a second mixture;
[0020] S4, adding steel fiber to the second mixture, stirring to obtain a concrete mixture;
[0021] S5. Cast the concrete mixture into molds and cure it to the specified age.
[0022] Optionally, in S1, the method for preparing the montmorillonite nanosheet raw material includes: mixing montmorillonite powder and chitosan in a mass ratio of (1.5-2.5):1, adding the mixture into deionized water, stirring evenly, performing ball milling and peeling, and vacuum drying the ball milled product to obtain the montmorillonite nanosheet raw material.
[0023] Optionally, the stirring method includes: stirring at a rotation speed of 355-365 rpm for 30-40 min.
[0024] Optionally, the ball milling peeling method is: continuous ball milling at a rotation speed of 400-450 rpm / min for 10-12 hours.
[0025] Optionally, in S1, the montmorillonite nanosheet raw material, phytic acid and urea are mixed into an acidic mixed solution, heated to 120-150° C. and stirred in a nitrogen environment, cooled and purified by washing with anhydrous ethanol, then rinsed three times with acetone and cooled and dried to obtain montmorillonite nanosheets.
[0026] Optionally, acetic acid is used to adjust the pH value of the mixed solution to 3-3.5.
[0027] Optionally, in S2, the mixing method is stirring at a rotation speed of 75-85 rpm for 2-3 min.
[0028] Optionally, in S3, the method for preparing the aqueous dispersion of montmorillonite nanosheets comprises: mixing the montmorillonite nanosheets obtained in S1 with water, and then dispersing the mixture by ultrasonic wave for 1 to 1.5 hours.
[0029] Optionally, in S3, the stirring method includes: stirring at a rotation speed of 75-85 rpm for 3-5 min.
[0030] Optionally, in S4, the stirring method includes: stirring at a rotation speed of 355-365 rpm for 1-2 min.
[0031] Optionally, in S5, the curing method includes: performing curing under standard curing conditions: the curing temperature is 20±2°C, and the relative humidity is >95%RH.
[0032] Thirdly, the application of the above-mentioned ultra-high performance concrete includes: application in protective engineering and disaster prevention and mitigation engineering.
[0033] Optional, including applications in bulletproof layers, main structures of long-span bridges and high-rise buildings.
[0034] The beneficial effects of the present invention are:
[0035] 1. The present invention adds montmorillonite nanosheets to ultra-high performance concrete. The fully dispersed montmorillonite nanosheets can form strong supramolecular compounds (CPN) after being modified by nitrogen-containing compounds and phosphorus-containing compounds. CPN has ultra-high bond energy that exceeds van der Waals forces and hydrogen bonds, greatly improving the integrity of the material in microstructure, thereby improving the material's anti-penetration performance. In addition, the oxygen-containing functional groups in montmorillonite are hydrophilic, and their complexation with calcium ions in cement can promote the formation of strong covalent bond CSH gels, replacing the relatively weak van der Waals forces in the original hydration products. Montmorillonite has a strong adsorption capacity and can adsorb water molecules and cations in cement-based materials. Through adsorption, new microstructures are generated between layers, thereby promoting the hydration reaction in cement, so that a denser microstructure and hydration product network are formed around the montmorillonite. The weaker van der Waals forces on the montmorillonite nanosheets are replaced by stronger hydrogen bonds, and strong supramolecular compounds are generated, providing active sites for the hydration products, which can promote the nucleation and crystal growth of calcium hydroxide in the hydration products, thereby improving the early strength and hydration rate of the cement-based matrix. Therefore, the improvement of material performance by montmorillonite is mainly attributed to the improvement of pore structure: the combination of the interface transition zone can be enhanced through complexation with calcium ions; the layered structure and high specific surface area of montmorillonite and the generation of hydrated crystals can play a role in blocking and filling pores and gaps, greatly improving the integrity of the cement-based structure; the addition of montmorillonite inhibits the generation of corrosive compounds (ettringite), greatly improving the anti-penetration performance.
[0036] 2. The integration of montmorillonite with phosphorus-containing compounds and nitrogen-containing compounds will become a very promising enhanced polymer flame retardant material. Phytic acid is a biological organic phosphorus-containing compound that can be used as a green and environmentally friendly alternative to petroleum and natural gas derivative flame retardant materials; urea rich in nitrogen can be used as a source of flame-retardant gas, and the raw material source is green and environmentally friendly. The combination of the three can greatly improve the flame retardancy and fire resistance of concrete. The layered structure of montmorillonite can catalyze the formation of a carbon layer in the polymer during combustion, effectively isolating oxygen and heat, and slowing down the burning rate of the material; the metal ions (iron ions) in montmorillonite have the ability to capture free radicals and can inhibit the chain reaction in combustion. Thereby improving the fire resistance of composite materials, it is conducive to their application in disaster prevention and mitigation projects. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0038] Figure 1 It is a schematic diagram of the process of preparing montmorillonite nanosheets in the preparation example.
[0039] Figure 2The figure is a relationship diagram between the compressive strength and flexural strength of the concrete materials prepared in the embodiment and the comparative example.
[0040] Figure 3 The figure is a relationship diagram between the penetration depth and the pit diameter of the concrete materials prepared in the embodiment and the comparative example. DETAILED DESCRIPTION
[0041] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0042] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0043] A typical embodiment of the present invention provides an ultra-high performance concrete, which is prepared from the following raw materials in parts by weight:
[0044] 1417-1517 parts of cement, 135-165 parts of silica fume, 35-43 parts of steel fiber, 21.16-63.48 parts of montmorillonite nanosheets, 410-510 parts of water and 8-14 parts of water reducing agent;
[0045] The montmorillonite nanosheets are modified by phytic acid and urea.
[0046] The present invention utilizes montmorillonite to modify ultra-high performance concrete: after the montmorillonite is added, its oxygen-containing functional groups complex with calcium ions in cement to promote the formation of strong covalent bond CSH gel and replace the relatively weak van der Waals force in the hydration product; at the same time, the bonding of the interface transition zone is enhanced, the microstructure is improved, and the integrity of the cement-based material is improved; the montmorillonite nanosheets are modified with phosphorus-containing compounds and nitrogen-containing compounds to form a strong supramolecular compound (CPN) with ultra-high bond energy (surpassing van der Waals force and hydrogen bond), which greatly improves the integrity of the material in terms of microstructure; the above principle can significantly improve the anti-penetration performance of the ultra-high performance concrete matrix under the action of high-speed projectiles.
[0047] The strong supramolecular compound (CPN) refers to: chitosan, phytic acid, and urea modified montmorillonite; the breaking of the chemical bonds of CPN requires higher energy, so it has better energy absorption capacity, thereby improving the compressive strength and anti-penetration performance of concrete; and because it has similar properties to hydration products, it can fill gaps and increase the integrity of the material; during the preparation process, montmorillonite MMT is first exfoliated by ball milling with the help of chitosan, and then further co-assembled with phytic acid and urea to form a nanohybrid CPN@MMT. Related research can be found in the technical document "DOI:10.1016 / j.conbuildmat.2024.136721.".
[0048] Optionally, the cement is 52.5 grade or 52.5R grade Portland cement or ordinary Portland cement.
[0049] Optionally, the amorphous silicon dioxide content in the silica ash is greater than 95wt%, and the specific surface area of the silica ash is greater than 21.0m 2 / g, and its specific density is greater than 2.2; the silica fume used in the present invention is an ultra-fine dry powder that has not been completely densified.
[0050] Optionally, the steel fiber is a copper-plated straight steel fiber with an average length of 13 mm and an average diameter of 0.16 mm; its tensile strength is greater than 2500 MPa, elastic modulus is 200 GPa, and density is 7800 kg / m 3 .
[0051] Optionally, the water reducer is a polycarboxylic acid-based high-efficiency water reducer with a water reduction rate greater than 25%.
[0052] A typical embodiment of the present invention provides a method for preparing the above-mentioned ultra-high performance concrete, comprising the following steps:
[0053] S1, mixing a montmorillonite nanosheet raw material, a phosphorus-containing compound and a nitrogen-containing compound in a set ratio, heating to 120-150° C. in an oxygen-free environment and stirring to obtain a montmorillonite nanosheet;
[0054] S2, mixing cement and silica fume to obtain a first mixture;
[0055] S3, adding the aqueous dispersion of montmorillonite nanosheets and a water reducing agent to the first mixture, stirring to obtain a second mixture;
[0056] S4, adding steel fiber to the second mixture, stirring to obtain a concrete mixture;
[0057] S5. Pour the concrete mixture into shape and cure it to the specified age.
[0058] In the above process, ultra-high performance concrete containing montmorillonite nanosheets is prepared. Montmorillonite nanosheets are added in the form of water dispersion, which can be fully dispersed in the concrete matrix to form a homogeneous concrete matrix, promote the adsorption capacity of montmorillonite, adsorb water molecules and cations in cement-based materials, and produce new microstructures between layers, thereby promoting the hydration reaction in cement, so that a more compact microstructure and hydration product network are formed around montmorillonite. In addition, uniformly dispersed active sites are provided for hydration products in the concrete matrix, which can promote the nucleation and crystal growth of calcium hydroxide in the hydration products, thereby improving the early strength and hydration rate of the cement-based matrix; giving full play to the strengthening effect of CPN.
[0059] Optionally, in S1, the method for preparing the montmorillonite nanosheet raw material includes: mixing montmorillonite powder and chitosan in a mass ratio of (1.5-2.5):1, adding the mixture into deionized water, stirring evenly, performing ball milling and peeling, and vacuum drying the ball milled product to obtain the montmorillonite nanosheet raw material.
[0060] Optionally, the stirring method includes: stirring at a rotation speed of 355-365 rpm for 30-40 min at room temperature to achieve uniform dispersion of montmorillonite powder and chitosan.
[0061] Optionally, the ball milling exfoliation method is: continuous ball milling at a rotation speed of 400-450 rpm / min for 10-12 hours, the ball milling temperature is room temperature, the purpose of ball milling is to promote the polymer molecular chains to enter the montmorillonite layers to achieve a better intercalation effect, and then vacuum drying in an environment of 60-70°C; during the ball milling process, chitosan is adsorbed on the montmorillonite nanosheets, promoting its dispersion in subsequent steps, and realizing the exfoliation and exfoliation of the montmorillonite nanosheets on the montmorillonite powder.
[0062] Optionally, in S1, montmorillonite nanosheet raw material, phytic acid and urea are mixed in a ratio of (1~2) g: (2~5) mL: (2~5) g to form an acidic mixed solution, heated to 120~150°C and stirred in a nitrogen environment, and washed with anhydrous ethanol after cooling. During the washing process, anhydrous ethanol dissolves the incompletely reacted phytic acid and urea, removes unreacted organic matter or impurities on the surface, and can reduce moisture and dry quickly. In addition, the use of ethanol can also avoid adverse oxidation reactions; then rinse with acetone three times and cool and dry to obtain solid montmorillonite nanosheets; at this time, the CPN generated by the four components of montmorillonite nanosheets, chitosan, phytic acid and urea has an ultra-high bond energy that exceeds the van der Waals force and hydrogen bond energy. Its dispersion in the concrete matrix can greatly improve the integrity of the material, thereby improving the material's anti-penetration performance.
[0063] Optionally, acetic acid is used to adjust the pH value of the mixed solution to 3-3.5 to provide an acidic environment to prevent the phytic acid from being neutralized.
[0064] Optionally, in S2, the mixing method is stirring at a rotation speed of 75-85 rpm for 2-3 min, and low-speed stirring can prevent powder splashing.
[0065] Optionally, in S3, the method for preparing an aqueous dispersion of montmorillonite nanosheets includes: mixing the montmorillonite nanosheets obtained in S1 with 70 wt % or all of the water in the mixture, and then performing ultrasonic dispersion for 1 to 1.5 hours to achieve uniform dispersion of the montmorillonite nanosheets in water.
[0066] Optionally, in S3, the stirring method includes: stirring at a rotation speed of 75-85 rpm for 3-5 min, and low-speed stirring can prevent powder splashing.
[0067] Optionally, in S4, the second mixture is stirred at a speed of 155-165 rpm for 3-5 min. After the second mixture shows good fluidity, steel fibers are slowly added through a square hole sieve and stirred. The subsequent stirring method includes: stirring at a speed of 355-365 rpm for 1-2 min to quickly mix the steel fibers.
[0068] Optionally, in S5, during the pouring process, a vibrating table can be used to lightly vibrate for 1 to 2 minutes, which helps to expel bubbles and improve its density; after pouring, cover with plastic film to prevent surface moisture loss, and demould after 20 to 28 hours.
[0069] Optionally, in S5, the curing method includes: performing curing under standard curing conditions: the curing temperature is 20±2°C, and the relative humidity is >95%RH.
[0070] A typical embodiment of the present invention provides the application of the above-mentioned ultra-high performance concrete, including: application in protective engineering and disaster prevention and mitigation engineering.
[0071] Specifically including: application in bullet-proof layers, main structures of long-span bridges and high-rise buildings.
[0072] Preparation Example
[0073] The preparation method of montmorillonite nanosheets, such as Figure 1 As shown, the following steps are included:
[0074] S11. Mix 2 g of montmorillonite powder with 1 g of chitosan, and suspend them in 250 mL of deionized water. Stir at a speed of 355-365 rpm (high-speed stirring) for 30 min at room temperature to obtain a montmorillonite powder dispersion.
[0075] S12, taking the montmorillonite powder dispersion and placing it in a grinding bowl, using a ball mill at 400 rpm / min for continuous ball milling for 10 hours for exfoliation, and drying the obtained product under a vacuum environment at 60° C. to obtain an exfoliated product.
[0076] S13, taking 1 g of the peeled product and immersing it in 200 mL of a mixed solution (the solvent is water) containing 3 g of urea and 3 ml of phytic acid, adjusting the pH to 3 with acetic acid, and transferring the mixed liquid to a glass flask;
[0077] S14: The liquid in the glass flask was stirred at 120° C. under nitrogen for 5 h and then cooled, and then poured into 300 mL of ethanol for washing, and then rinsed with acetone and cooled and dried three times to collect the modified solid montmorillonite nanosheets.
[0078] In the above process, montmorillonite is prepared by a two-step process of stripping and modification. The four components of montmorillonite nanosheet raw material, chitosan, urea and phytic acid form a strong supramolecular compound (CPN), which is used to modify ultra-high performance concrete in the following examples.
[0079] The montmorillonite powder used in this preparation example is commercially available montmorillonite, and its typical molecular structure is (Na, Ca) 0.33 (Al,Mg)2(Si4O 10 )(OH)2·nH2O.
[0080] Example 1
[0081] An ultra-high performance concrete is prepared from the following raw materials in parts by weight:
[0082] 1467 parts of 52.5 grade ordinary Portland cement, 147 parts of silica fume, 21.16 parts of montmorillonite nanosheets obtained in the preparation example, 39 parts of steel fiber, 452 parts of tap water, and 8 parts of water reducing agent.
[0083] Among them, silica fume is an ultra-fine dry powder that is not fully densified, with an amorphous silicon dioxide content greater than 95wt% and a specific surface area greater than 21.0m 2 / g, specific density is greater than 2.2.
[0084] The steel fiber is a copper-plated straight steel fiber with an average length of 13mm and an average diameter of 0.16mm; its tensile strength is greater than 2500MPa, elastic modulus is 200GPa, and density is 7800kg / m 3 .
[0085] The water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent.
[0086] The preparation method comprises:
[0087] S1. Obtain montmorillonite nanosheets according to the method of the preparation example.
[0088] S2. Mix cement and silica fume, and stir at a rotation speed of 75-85 rpm for 2-3 min to obtain a first mixture.
[0089] S3. Add the aqueous dispersion of montmorillonite nanosheets and the water reducing agent in S1 to the first mixture, and stir at a rotation speed of 75-85 rpm for 3-5 min to obtain a second mixture; wherein the aqueous dispersion of montmorillonite nanosheets is prepared by mixing montmorillonite nanosheets with 320 parts of water and then ultrasonically dispersing the mixture for 1-1.5 hours.
[0090] S4. Stir the second mixture at a rotation speed of 155-165 rpm for 3-5 min. After the second mixture shows good fluidity, slowly add steel fiber to the second mixture through a square hole sieve, and then stir at a rotation speed of 355-365 rpm for 1-2 min to obtain a concrete mixture; wherein good fluidity means that the cementitious material can be well mixed, and no obvious unhydrated material emerges on the surface of the fresh concrete.
[0091] S5. Pour the concrete mixture into shape, use a vibrating table to lightly vibrate for 1 to 2 minutes during the pouring process, cover it with plastic film after pouring to prevent surface moisture loss, and demould after 20 to 28 hours; then cure it under standard curing conditions (temperature is 20±2℃, relative humidity>95%RH) to the specified age.
[0092] Example 2
[0093] An ultra-high performance concrete is prepared from the following raw materials in parts by weight:
[0094] 1467 parts of 52.5 grade ordinary Portland cement, 147 parts of silica fume, 42.32 parts of montmorillonite nanosheets obtained in the preparation example, 39 parts of steel fiber, 452 parts of tap water, and 10.5 parts of a water reducing agent.
[0095] The raw material specification requirements and preparation method are the same as those in Example 1.
[0096] Example 3
[0097] An ultra-high performance concrete is prepared from the following raw materials in parts by weight:
[0098] 1467 parts of 52.5R grade ordinary Portland cement, 147 parts of silica fume, 63.48 parts of montmorillonite nanosheets obtained in the preparation example, 39 parts of steel fiber, 452 parts of tap water, and 13 parts of a water reducing agent.
[0099] The raw material specification requirements and preparation method are the same as those in Example 1.
[0100] Example 4
[0101] An ultra-high performance concrete is prepared from the following raw materials in parts by weight:
[0102] 1467 parts of 52.5R grade ordinary Portland cement, 147 parts of silica fume, 84.56 parts of montmorillonite nanosheets obtained in the preparation example, 39 parts of steel fiber, 452 parts of tap water, and 14 parts of a water reducing agent.
[0103] The raw material specification requirements and preparation method are the same as those in Example 1.
[0104] Comparative Example 1
[0105] An ultra-high performance concrete is prepared from the following raw materials in parts by weight:
[0106] 1467 parts of 52.5R grade ordinary Portland cement, 147 parts of silica fume, 39 parts of steel fiber, 452 parts of tap water, and 4 parts of water reducer.
[0107] The difference from Example 1 is that no montmorillonite nanosheets are added and the amount of water reducing agent is adjusted accordingly.
[0108] Other raw material requirements and preparation methods are the same as those in Example 1.
[0109] Comparative Example 2
[0110] An ultra-high performance concrete is prepared from the following raw materials in parts by weight:
[0111] 1467 parts of 52.5 grade ordinary Portland cement, 147 parts of silica fume, 21.16 parts of montmorillonite powder, 39 parts of steel fiber, 452 parts of tap water, and 8 parts of water reducer.
[0112] The difference from Example 1 is that the montmorillonite powder adopts the purchased raw material in the preparation example, and does not undergo the peeling and modification treatment shown in S11 to S14 in the preparation example.
[0113] Other raw material requirements and preparation methods are the same as those in Example 1.
[0114] Conventional mechanical tests and high-speed projectile penetration resistance tests were performed on the ultra-high performance concrete of the above-mentioned embodiments and comparative examples, and the results are shown in Table 1. The high-speed projectile penetration resistance test process is the same as that of the Chinese patent application with application number 2023117815297 (a kind of anti-penetration ultra-high performance concrete and preparation method and application), but the target speed is increased from 400m / s to 650m / s.
[0115] Table 1 Results of conventional mechanical tests and anti-high-speed projectile penetration performance tests
[0116]
[0117] Note: Penetration depth refers to the distance from the impact surface of the target to the deepest point of the crater;
[0118] The crater diameter is the diameter of an equivalent circle with the same area as the target crater;
[0119] The crater volume refers to the volume of the target crater.
[0120] By comparing Table 1, it can be found that the compressive strength, elastic modulus and tensile strength of the examples are improved to varying degrees compared with those of Comparative Examples 1 and 2. With the increase of the content of montmorillonite, the static mechanical properties are enhanced accordingly. However, after reaching a certain threshold, further increasing the content of montmorillonite has little effect on the performance improvement of ultra-high performance concrete. It can be seen that the significant improvement in compressive strength is mainly attributed to: the nanoscale of montmorillonite enables it to effectively fill the micropores in the cement matrix, significantly improve the density of concrete, and reduce the porosity; at the same time, montmorillonite has an extremely high specific surface area and has the ability to adsorb water molecules and cations. When montmorillonite is dispersed in cement-based materials, it can form a new bonding network at the microscopic level by inserting ions between layers, promote the formation of CSH gel and the growth of hydrated crystals, and form a more compact microstructure.
[0121] The significant improvement in elastic modulus is mainly attributed to the fact that the oxygen-containing functional groups of montmorillonite can form complexes with calcium ions in the cement matrix, significantly enhancing the interfacial strength between the cement matrix and aggregate. The ITZ is the most vulnerable area in concrete, and montmorillonite plays a reinforcing role in this area, thereby increasing the elastic modulus of the material. At the same time, montmorillonite promotes the formation of CSH gel, which is the main bonding material in the cement hydration process and can significantly enhance the mechanical properties of concrete. Through the catalytic effect of montmorillonite, more CSH gel is generated, further improving the rigidity of the material.
[0122] The significant improvement in flexural strength is mainly attributed to the fact that the layered structure of montmorillonite can effectively inhibit the expansion of cracks and play a blocking role in the cracks, thereby increasing the flexural strength of the material. At the same time, the layered structure and swelling and water absorption characteristics of montmorillonite can also improve the toughness of the material.
[0123] The significant improvement in the penetration resistance of ultra-high performance concrete is mainly attributed to the following: 1) Montmorillonite greatly improves the impact and penetration resistance of concrete. Montmorillonite effectively resists the intrusion of external impact loads by improving the pore structure and enhancing the density of the microstructure, reducing the penetration depth and significantly improving the performance of concrete under impact loads. 2) The reduction in the pit diameter shows the effectiveness of montmorillonite in resisting impact damage. Montmorillonite can reduce surface damage caused by impact through filling and reinforcement effects. The expansion of cracks caused by impact loads is organized through bridging action, reducing the surface damage area. At the same time, the dense and uniform distribution of the material improves the toughness of the material and reduces the material damage caused by stress concentration.
[0124] Therefore, the present invention provides an ultra-high performance concrete with excellent resistance to high-speed projectile penetration and mechanical properties, and its penetration resistance is significantly higher than that of the ultra-high performance concrete without montmorillonite modifier in comparative example 1. It can be seen that the strong supramolecular compound and CSH gel formed by the addition of montmorillonite modifier are beneficial to improving the penetration resistance of ultra-high performance concrete; on the one hand, montmorillonite modifier can promote the production of CSH gel and hydrate crystals in ultra-high performance concrete, forming a denser microstructure and improving the mechanical properties of the material; on the other hand, montmorillonite modifier can provide more attachment sites to facilitate the generation and expansion of hydrate crystals, repair the pores and cracks in the transition zone between the matrix and the interface, and greatly improve the penetration resistance of the material. The optimization of the penetration resistance and mechanical properties of ultra-high performance concrete by montmorillonite modifier enables it to be used as a modern new protective material.
[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An ultra-high performance concrete, characterized in that: The invention is prepared from the following raw materials in parts by weight: 1417-1517 parts of cement, 135-165 parts of silica fume, 35-43 parts of steel fiber, 21.16-63.48 parts of montmorillonite nanosheets, 410-510 parts of water and 8-14 parts of water reducing agent; the montmorillonite nanosheets are modified by phytic acid and urea; The method for preparing the ultra-high performance concrete comprises the following steps: S1, mixing montmorillonite nanosheet raw material, phytic acid and urea in a set ratio, heating to 120-150° C. in an oxygen-free environment and stirring to obtain montmorillonite nanosheets; S2, mixing cement and silica fume to obtain a first mixture; S3, adding the aqueous dispersion of montmorillonite nanosheets and a water reducing agent to the first mixture, stirring to obtain a second mixture; S4, adding steel fiber to the second mixture, stirring to obtain a concrete mixture; S5, casting the concrete mixture into molds and curing it to the specified age; In S1, the preparation method of the montmorillonite nanosheet raw material includes: mixing montmorillonite powder and chitosan in a mass ratio of (1.5~2.5):1, adding the mixture into deionized water, stirring evenly, performing ball milling and peeling, and vacuum drying the ball milled product to obtain the montmorillonite nanosheet raw material; mixing the montmorillonite nanosheet raw material, phytic acid and urea in a ratio of (1~2) g: (2~5) mL: (2~5) g to form an acidic mixed solution, heating to 120~150°C and stirring under a nitrogen environment, cooling and purifying with anhydrous ethanol to obtain montmorillonite nanosheets; and adjusting the pH value of the mixed solution to 3~3.5 using acetic acid.
2. The ultra-high performance concrete according to claim 1, characterized in that: The cement is 52.5 grade or 52.5R grade silicate cement or ordinary silicate cement; the content of amorphous silicon dioxide in the silica fume is greater than 95wt%, and the specific surface area of the silica fume is greater than 21.0m 2 / g, and a specific density greater than 2.2; the steel fiber is a copper-plated straight steel fiber with an average length of 13 mm and an average diameter of 0.16 mm; and the water reducer is a polycarboxylic acid-based high-efficiency water reducer.
3. A method for preparing ultra-high performance concrete according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1, mixing montmorillonite nanosheet raw material, phytic acid and urea in a set ratio, heating to 120-150° C. in an oxygen-free environment and stirring to obtain montmorillonite nanosheets; S2, mixing cement and silica fume to obtain a first mixture; S3, adding the aqueous dispersion of montmorillonite nanosheets and a water reducing agent to the first mixture, stirring to obtain a second mixture; S4, adding steel fiber to the second mixture, stirring to obtain a concrete mixture; S5, casting the concrete mixture into molds and curing it to the specified age; In S1, the preparation method of the montmorillonite nanosheet raw material includes: mixing montmorillonite powder and chitosan in a mass ratio of (1.5~2.5):1, adding the mixture into deionized water, stirring evenly, performing ball milling and peeling, and vacuum drying the ball milled product to obtain the montmorillonite nanosheet raw material; mixing the montmorillonite nanosheet raw material, phytic acid and urea in a ratio of (1~2) g: (2~5) mL: (2~5) g to form an acidic mixed solution, heating to 120~150°C and stirring under a nitrogen environment, cooling and purifying with anhydrous ethanol to obtain montmorillonite nanosheets; and adjusting the pH value of the mixed solution to 3~3.5 using acetic acid.
4. The method for preparing ultra-high performance concrete according to claim 3, characterized in that: In S1, the stirring method includes: stirring at a rotation speed of 355-365 rpm for 30-40 min; the ball milling peeling method includes: continuously ball milling at a rotation speed of 400-450 rpm / min for 10-12 h.
5. The method for preparing ultra-high performance concrete according to claim 3, characterized in that: In S3, the method for preparing the aqueous dispersion of montmorillonite nanosheets comprises: mixing the montmorillonite nanosheets obtained in S1 with water, and then dispersing the mixture by ultrasonication for 1 to 1.5 hours.
6. The method for preparing ultra-high performance concrete according to claim 3, characterized in that: In S2, the mixing method is stirring at a speed of 75-85 rpm for 2-3 min; In S3, the stirring method includes: stirring at a speed of 75-85 rpm for 3-5 min; in S4, the stirring method includes: stirring at a speed of 355-365 rpm for 1-2 min; in S5, the curing method includes: performing under standard curing conditions: the curing temperature is 20±2°C, and the relative humidity is >95%RH.
7. An application of the ultra-high performance concrete according to any one of claims 1 to 2, characterized in that: include: Application in protective engineering and disaster prevention and mitigation engineering; including: application in bullet-proof layers, main structures of large-span bridges and high-rise buildings.
Citation Information
Patent Citations
Epoxy resin / montmorillonite nanometer composite paint used on metal surface and application of epoxy resin / montmorillonite nanometer composite coating
CN109796845A
Preparation method of phytic acid modified magnesium-aluminum hydrotalcite / montmorillonite nano material
CN114621771A